Reference values for fetal Doppler-based cardiocirculatory indices in monochorionic-diamniotic twin pregnancy - Thananan Chongsomboonsuk (BMC, 2021)
Abstract Background Placental anastomoses in monochorionic diamniotic (MCDA) twin pregnancy have a major impact on fetal circulation. This study was designed to define reference ranges of cardiac and vascular Doppler indices in MCDA twin pregnancies. Methods This cross-sectional study included 442 uncomplicated MCDA twin fetuses undergoing Doppler ultrasonography at 18–35 weeks of gestation. Left and right myocardial performance index (LV-MPI, RV-MPI), E/A ratio of atrioventricular valves, pulsatility indices of umbilical artery, middle cerebral artery (MCA), and ductus venosus (DV), cerebroplacental ratio, peak systolic velocity of MCA, S/a ratio of DV, and early diastolic filling time of ductus venosus (DV-E) were evaluated under standardized settings. The equation models between Doppler indices and gestational age (GA) were fitted. After adjustment for GA, the correlations between MPI and fetal heart rate (FHR), and between MPI and DV indices were analyzed. Results Estimated centiles of Doppler indices were derived as a function of GA, being distinct in values from those of singletons. There was no correlation between GA-adjusted MPI and FHR. DV-E was inversely related to LV-MPI. Conclusions MCDA twins showed significant changes in some Doppler indices throughout gestation with quantitative differences from singletons, emphasizing the importance of MC twin-specific reference values for clinical application. Further adjustment of MPI for FHR was unnecessary. DV-E is a vascular index indirectly representing fetal diastolic function.